CLINICAL AND PARACLINICAL CHARACTERISTICS AND TREATMENT OUTCOMES OF THALASSEMIA IN PEDIATRIC PATIENTS UNDER 15 YEARS OF AGE AT PEDIATRIC DEPARTMENT 1, LAO CAI PROVINCIAL GENERAL HOSPITAL NO. 1 (Vietnam Journal of Community Medicine, 2026)
Objective: Describes the clinical and paraclinical characteristics and evaluates the treatment outcomes of thalassemia in patients under 15 years of age at the Pediatric Department 1 – Lao Cai Provincial General Hospital No. 1.Research methods: A cross-sectional descriptive study was conducted on 133 pediatric patients under 15 years of age with a confirmed diagnosis of thalassemia who were receiving treatment at Lao Cai Provincial General Hospital No. 1 from March 2025 to November 2025.Results: The pediatric patients had a mean age of 8.6 ± 3.4 years. β-thalassemia was the predominant type (87.2%); most children were diagnosed after 1 year of age (80.5%) and commonly presented with severe anemia (73.7%) accompanied by marked iron overload (over 60% with ferritin >1500 ng/mL). Blood transfusion significantly improved hemoglobin levels from 69.1 ± 13.9 g/L to 100.09 ± 17.52 g/L (p < 0.05) and was relatively safe, with no severe complications recorded. However, treatment adherence remained limited, with adherence rates of 52.6% for regular blood transfusion and intravenous iron chelation, 27.1% for oral iron chelation, and 46.6% for regular follow-up, while irregular adherence was still high (61.7%).Conclusion: Blood transfusions provide significant and safe improvements in hemoglobin levels, but treatment adherence rates, particularly to oral chelation therapy and follow-up appointments, remain low. Improved management, counseling, and family support are needed to enhance treatment efficacy and quality of life for children.
Keywords: Treatment outcomes, pediatric patients, Thalassemia